An updated investigation of cancer incidence and mortality at a Scottish semiconductor manufacturing facility with case-control and case-only studies of selected cancers. Issue 10 (19th June 2012) - Darnton, Andrew; Miller, Brian G; MacCalman, Laura; Galea, Karen S; Wilkinson, Sam; Cherrie, John W; Shafrir, Amy; McElvenny, Damien; Osman, John
Abstract : Objectives: An earlier investigation raised concern that some cancer cases might be linked to work at a semiconductor manufacturing plant. The aim of this study was to describe an update of the cancer incidence and mortality of these workers and assess whether workplace exposures contributed to any increased risk of selected cancers. Methods: Standardised mortality ratios and standardised incidence ratios were calculated for cancer site groups of a priori interest in a cohort previously flagged against the National Health Service Central Register, with follow-up extended to the 2007 for deaths and 2006 for cancer registrations. Cases of female breast cancer, lung and stomach cancer, and male brain cancer, and a random sample of control subjects individually age-matched to the breast cancer cases, were identified from within the cohort dataset and invited to participate via General Practitioners. Exposures were estimated using a job exposure matrix developed from a historical hygiene assessment and assigned to job histories obtained from personal interview of subjects (or proxies). Results: Though the findings were uncertain, there were no excesses of mortality or cancer incidence, either overall or for specific cancer sites, suggestive of a workplace effect. Logistic regression analyses comparing 20 cases of breast cancer with 83 matched controls showed no consistent evidence of any relationship with occupational exposures. Assessment of commonalities of workplace exposures among case sets for other cancer types was limited by the small numbers. Conclusions: These results do not support earlier concerns about occupational cancer risks among this cohort.